Duplex collecting system; (complicated and uncomplicated) report of two cases with literature review - Khalid Mohammad Qasem; Zamaryalai Hakimi; Salmai Turial; Turyalai Hakimi; Mohammad Anwar Jawed (Elsevier, 2022)
Duplex collecting system is a urinary tract defect that represents a condition where upper and lower pole moieties fuse incompletely. Duplication could be complete or partial (Y-shaped ureter). We report two cases (complicated and uncomplicated) of unilateral duplicated collecting system with a Y-shaped ureter. The first (complicated) case was diagnosed as having kidney stone and treated surgically. The second (uncomplicated) case was diagnosed incidentally during a routine check-up. As there were no other associated urinary tract anomalies, our team advised the patient's parents to seek regular follow-up by a pediatric surgeon (for the development of possible urinary tract infection and calculus which are more prevalent in low-resource settings). Both patients were followed-up for six months in satisfactory condition.